2019
DOI: 10.7596/taksad.v8i3.2243
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of Learning: An Investigation on Educational Technologies

Abstract: The paper discusses various approaches to the concept of "individualization of learning" and their relevant changes in connection with the development of educational technologies. An analysis of the relevant literature shows that a more precise content of this concept in each specific case depends on what goals are meant when talking about individualization. There are large differences found in different countries, among different authors, and in everyday educational practice when this concept is used. More th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This particular finding is similar to what users found in the massive open online courses (MOOC). Whereby Karpenko et al (2019) found out that students were not satisfied with the quality of communication and individualization of learning. So, EdCrunch Academy Training program's structured and the course organization has some flaws that leave the trainees dissatisfied.…”
Section: Discussionmentioning
confidence: 99%
“…This particular finding is similar to what users found in the massive open online courses (MOOC). Whereby Karpenko et al (2019) found out that students were not satisfied with the quality of communication and individualization of learning. So, EdCrunch Academy Training program's structured and the course organization has some flaws that leave the trainees dissatisfied.…”
Section: Discussionmentioning
confidence: 99%
“…The leading trends of modern education are individualization, personalization of educational process (Kargina, 2015;Karpenko et al, 2019;Kovaleva, 2017;Sazonov, 2020). Attention to these trends is explained by a change in people's socio-cultural way of life, manifested in normative, value and semantic spheres, which cause changes in education.…”
Section: Introductionmentioning
confidence: 99%